Structural MRI substrates of cognitive impairment in neuromyelitis optica. (27th October 2015) - Liu, Yaou; Fu, Ying; Schoonheim, Menno M.; Zhang, Nan; Fan, Moli; Su, Lei; Shen, Yi; Yan, Yaping; Yang, Li; Wang, Qiuhui; Zhang, Ningnannan; Yu, Chunshui; et al.
Abstract : Objective: To identify the clinical and structural MRI markers for predicting cognitive impairment (CI) in patients with neuromyelitis optica (NMO). Methods: Fifty-four patients with NMO and 27 healthy controls underwent extensive neuropsychological testing and multimodal 3.0T MRI. The patient group was classified as CI or cognitively preserved (CP), using a criterion of ⩽1.5 SD on at least 2 cognitive domains. MRI measurements included white matter (WM) lesion volume, gray matter (GM), WM, and deep GM (DGM) volume, cortical thickness, and the severity and extent of WM tract diffusion metric alterations based on fractional anisotropy and mean, axial, and radial diffusivity. Groups were compared using a multivariate general linear model, and clinical and MRI measurements were related to average cognition z scores by partial correlations and a stepwise linear regression model. Results: Twenty-six patients with NMO (48.2%) were classified as CI and showed WM tract diffusion abnormalities, particularly increased radial diffusivity, and GM especially DGM atrophy compared with healthy controls. Patients classified as CP also showed alterations of WM tract diffusion but without significant GM atrophy. Compared with the CP group, patients with CI demonstrated a lower level of education and decreased hippocampal volume. In the whole patient group, average cognition z scores were best predicted by the level of education and hippocampal volume ( R 2 = 0.46, p < 0.001). Conclusion: In patients with NMO, WM tract integrity disruption was identified in both CP and CI groups. GM atrophy, particularly in the DGM, was only found in the CI group. Hippocampal volume is the main MRI predictor of cognition in NMO.